Customisable peptide hydrogels as user-defined biomimetic models of specific tissue microenvironments - Curd, Johnathan (2022)
The extracellular matrix (ECM) is comprised of a complex variety of biochemically distinct molecules including proteins, glycoproteins, proteoglycans, and polysaccharides. These provide not only the physical support for resident cells but also play a vital role in tissue homeostasis, by providing key biophysical and biochemical cues which regulate cell growth, survival, motility, and differentiation. However, current in vitro models typically fail the recapitulate the complexities of the native ECM, leading to a poor extrapolation of in vitro findings to in vivo relevance. This is a major contributing factor to the high attrition rate of novel drug candidates moving from the lab to the clinic. This has driven the recent interest in the development of more sophisticated 3D in vitro models which allow customisation of stiffness and composition to better reflect in vivo tissues.